O contexto institucional do pólo farmacêutico em Goiás: cooperação e competição - Santos, Edna Perpétua dos (Universidade do Vale do Rio dos Sinos, 2010)
This study aims to analyze how the institutional context of a productive pole in Goiás helps achieve competitive gains for drug companies present in it. The institutional context is seen from theoretical perspectives of cooperation, competition, types of arrangements and relationships among characters geographically close. It is a geographical arrangement that has been studied as a single case, with sub-units of analysis, structured theoretical elements that reach beyond the characterization of partners, the ways and gains in their relationships. Empirically, informal relationships and actions of significant cooperation among were identified. Gains in learning, infrastructure, cost reduction, collective solutions, among others, were confirmed. However, lack of specific policies for the sector, opportunistic behavior, lack of evidence linking partners and high competition among firms can affect the bond of trust needed to build a more collaborative institutional environment. It is described how partners behave, which actions they develop and what are the results from the closeness and cooperation. We noticed significant growth in the pharmaceutical industry in the state of Goiás and Brazil. Prospects for new facilities, production increase, strong growth in sales and search for new markets are some of their goals. However, rather than collective actions occurred in the past, there is, in fact, a gap between deliberate cooperation for pharmaceutical companies in Goiás and points related to the delimitation of objectives, governance mechanisms rules set up and individual gains foreseeing from collective action, as some of the emerging needs for consolidation of cooperation between firms in the cluster.
Keywords: Cooperação; Competitividade; Arranjos produtivos; Indústria farmacêutica; Cooperation; Competitiveness; Production arrangements; Pharmaceutical industry; ACCNPQ::Ciências Sociais Aplicadas::Administração